DIGITAL LITERACY: TEACHERS CHALLENGES INTEGRATING GRAPHIC DESIGN TECHNOLOGY IN THE CLASSROOM - Kushiator, George; Klodzi, Innocent; Hamidu, Inusah (Penerbit Lafadz Jaya, 2023)
Since the development and introduction of digital technology in Ghana. The government has made the effort to supply computers to schools and individuals to accentuate the digital literacy in schools and colleges. Since then, most visual art teachers have not been able to integrate the use of information and communication technology in teaching students in the classroom Therefore, exploiting the use of Information and Communications Technology (ICT) in the visual arts classroom has been rather challenging. As a result, there is an urgent need to investigate these factors as they influence negatively on the young Senior High Schools graphic design students to become digital literate in the 21st century. The study therefore investigates the challenges design teachers face in teaching graphic design in t schools in the wake of the 21st century. This study uses a descriptive survey method. The study was conducted quantitatively where questionnaires were designed and distributed to 10 art teachers using simple random sampling. Employing the purposive sampling methodology in the selected Senior High School in where visual arts is taught in the Ho Municipality. The outcome of this study revealed that GD teachers do not make use of ICT in teaching graphic design in schools. it is recommended that teachers should be trained to use ICT software to teach and impart knowledge in the classroom